An introduction to 'Making the city "home": Practices of belonging in Pacific cities'. (21st July 2022) - Kraemer, Daniela; Stern, Monika
Abstract: It is estimated that by 2050, 50% of Pacific peoples will be living out their full lives in cities and towns throughout Oceania and around the world. Over the last 35 years, previous patterns of circular migration have been giving way to permanent urban settlers and to generations born and raised in urban places. These 'urbanites' demonstrate a firm commitment to urban living in both the present and the future. In the cities, Pacific people have been building roots and making the city 'home'. This special issue focuses on some of the diverse practices Pacific urbanites employ in creating 'home', which we define as the context where they centre their social, cultural and economic worlds and the place in which they see themselves living out their aspirations and future life course. Practices range from the use of graffiti, sharing music, playing reggae, the role of artists and exhibitions, and mobile phone use. In doing so, this special issue contributes to a growing body of work focused on the ways urban‐based Pacific peoples contest essentialising stereotypes that deny their legitimacy and dismiss their urban experiences as less authentic. The collection of papers demonstrates how Pacific peoples are imagining and demonstrating their identities as Pacific urbanites reflecting their commitment to an urban Pacific, national, cultural and political belonging.